Language and students’ access to psychological support at a South African university - Payi, Gwen Sinamava (Rhodes University, 2026)
It is no new knowledge that in South Africa, language has historically functioned both as a tool of oppression during apartheid and as a resource for transformation in the post-apartheid higher education (HE) landscape. In multilingual and culturally diverse contexts such as South African universities, language plays a critical role in shaping students’ access to and experiences of university life—not only in the transformation of teaching and learning but also in essential student services, particularly psychological support, which is central to students’ holistic well-being and academic success. This thesis explores the intersection of language, psychological support, and institutional language policy at Rhodes University, with a specific focus on how students who speak African languages as Mother Tongue experience and access mental health services in an institution that proclaims a commitment to multilingualism, as well as the experiences and perspectives of psychologists who provide those services. Anchored in the field of Language Planning and Policy (LPP), this study critically examines how language practices within the university’s Student Counselling Centre (SCC) align—or do not align— with the linguistic needs of a culturally and linguistically diverse student body. Using a qualitative case study approach, questionnaires and semi-structured interviews were conducted with both students and psychologists to explore their lived language related experience in psychological counselling, institutional language policy framework, and the implication of professional psychology training and curriculum. Findings reveal that while students possess functional proficiency in English, they encounter emotional strain, linguistic anxiety, and cognitive challenges when counselling takes place in a language other than their Mother Tongue—challenges that are intensified by institutional power dynamics privileging English and, to a lesser extent, isiXhosa. These dynamics, coupled with the absence of formal language negotiation practices and a perceived linguistic hierarchy, contribute to emotional withdrawal, reduced trust in the counselling process, and in some cases, discontinuation of counselling services. This study contributes towards the ongoing discourse on the transformation of HE and psychological practice in South Africa by making a strong case for more linguistically inclusive and culturally grounded approaches in student support services. It calls for a reimagining of multilingualism not only as a pedagogical imperative but as a practical necessity for equitable access to mental health care and other essential services in universities.
an exploratory case study
Keywords: Uncatalogued